Quantitative Methods in Forest Ecology - Srivastava, P. B. L. (Indian Forester, 1974)
The collection and interpretation of ecologica1 information and its application is essential for developing precision in the scientific management of forests. Syn-ecological concepts of succession of plant communities and indicator value of species in relation to environmental factors, chiefly climatic or climato-edaphic conditions are important guiding principles for successful application techniques towards a natural regeneration and for deriving full benefits from the protective role and other conservational roles of the forest vegetation complex. These externalities will perhaps, in course of time, outweigh the direct benefits from the productive potential of forests. Until such time, it is necessary to evaluate the role of forests in terms of production, namely, to determine growth requirements of individual species (aut-ecological spects) and the effect of environmental factors such as light, temperature, moisture, soil, etc., on them in order to raise successful monocultures which is the need of the day in the context of mass production technology. This requires collection of data with the help of suitable statistically valid methods based on adiquate sampling and functional procedures. As is well known, ecologically two broad types of formations occur in this country, namely, (1)more or less pure tree communities having gregarious occurrence of a few dominant species on large areas with sharp ecotomal belts (e.g., sal and chir), and (2) mixed commodities having a few to many species in dominant and codominant position where tension belts are not sharply delineated (e.g., mixed dry deciduous, moist deciduous, semi-evergreen and evergreen forests). Needless to say, the methods, intensity and mature sampling adopted in these two broad types will be different. Ecological studies based on simple line transects and quadrats in such highly complex forest eco-systems of the tropics with rapid changes in climatic, edaphic and biotic conditions will not be efficient and conclusions from such studies which tend to oversimplify the picture are bound to be misleading. Very few attempts have been made in this country to evolve suitable methods of studying vegetation according to specific needs and ends. Even in the case of those sporadic studies the data on site factors have not been collected and correlated with the community attributed with the same precision with which ecological studies were conducted, i.e, specfic correlation between vegetational parameters and environmental factors have not been worked out with the result that most of the studies are of very little applied value in forestry. The present article gives a background information of some of the important objects of syn-ecological studies, various methods and technical procedures in brief, techniques appropriate for analysing data of various degrees of complexity and emphasizes the need for developing efficient methods to suit diverse types of vegetation occurring in this country and objective analysis of the information thus gained to permit its practical application in the field, in the context of both productive and conservational functions of large masses of tree dominated vagetation complexes, whether natural or man-made, in the interests of harnessing the environment in the service of humanity.